Problem facing by private developer involving abandoned projects in Malaysia - Muhamad Abdul Hadi, Ahmad Sabri (2019)
The abandoned project has been one of the biggest problems in the country which has deprived the development in Malaysia since 1980s. Despite the ever-expanding era of growth in Malaysia, this remains an often issues in Parliament and social media. According to the official site of the National Housing Department, abandoned projects are defined as projects which meet the following criteria, which projects are not completed within or outside of the Sale and Purchase Agreement and no significant activity on the construction site during the six (6) months of continuous service; or winding-up petition has been filed in the High Court under Section 218 of the Companies Act 1966; or is placed under the Official Receiver and Manager (Receiver & Manager); or the developer is unable to acknowledge in writing to the Controller of Housing; Authorized and abandoned projects by the Ministry of Housing and Local Government under section 11 (1) (c) of Act 118. Abandoned Project Recovery Division 2017 report stated that there were 254 abandoned housing projects have been listed in Malaysia. Among of the issue that has been highlighted regarding this problem is the contribution of each stakeholder that involved within the construction of the projects which resulting in abandoned the project. Previous researches has identified private developer as root of causes of abandonment. By its relatively limited research on this issue, a study was conducted to investigate the problem facing by the private developer regarding this problem. Among the studies undertaken is to investigate the main problem facing by private developer, thus providing questionnaires to developer, engineer, consultant, local authorities and others to seek the views and detailed information from third parties that expertise in the industry on problems and ways to solve these problems. The perspective of the respondents has been analyzed and ranked based on Relative Importance Index (RII). Respondents stated that ‘private developer abandoned their projects due to unethical attitude of private developer resulting in misuse of project capital and fraudulence’ are the major problem that contributes in abandonment problems of abandoned housing in construction project. Finally, they are agreed that ‘amending the Housing Development Act of 1966 which provides for the control and licensing of the business of housing development in Peninsular Malaysia and the protection of the interest of the purchasers’ can help to minimize this abandonment problem.